2015
DOI: 10.1177/0961203315595131
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficacy and safety of tacrolimus, mycophenolate mofetil, and cyclophosphamide as induction therapy for lupus nephritis: a Bayesian network meta-analysis of randomized controlled trials

Abstract: Tacrolimus was the most efficacious induction treatment for patients with lupus nephritis, and had the highest probability of decreasing the risk of serious infections. Higher remission rates combined with a more favorable safety profile suggest that MMF is superior to CYC as induction treatment in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
(62 reference statements)
3
14
0
2
Order By: Relevance
“…5 A network analysis involving 9 trials in 972 patients concluded that tacrolimus was superior to cyclophosphamide for inducing complete or partial disease remission, whereas MMF was comparable to cyclophosphamide treatment. 6 The different conclusions drawn by these meta-analyses and the present study are likely due to the larger amount of information available in the present review to permit more precise inferences about competing treatments for lupus nephritis.…”
Section: Although Itmentioning
confidence: 70%
See 1 more Smart Citation
“…5 A network analysis involving 9 trials in 972 patients concluded that tacrolimus was superior to cyclophosphamide for inducing complete or partial disease remission, whereas MMF was comparable to cyclophosphamide treatment. 6 The different conclusions drawn by these meta-analyses and the present study are likely due to the larger amount of information available in the present review to permit more precise inferences about competing treatments for lupus nephritis.…”
Section: Although Itmentioning
confidence: 70%
“…In a complex condition with several options for treatment, of which some have not been directly compared in trials, a network meta-analysis offers the potential to compare all therapeutic strategies simultaneously within a single framework and rank treatments per efficacy and safety. Network analysis has been used to evaluate induction therapy in lupus nephritis, but results have been inconclusive due to relatively few included studies 5,6 or reporting of drug harms only. 7 METHODS…”
mentioning
confidence: 99%
“…Based on our study and previous meta-analyses27 28 there is level 1A evidence29 to support the clinical efficacy of TAC in the subgroup of Asian patients with LN. However, our study illustrated that a ‘grade A’ recommendation for TAC is hampered by the heterogeneity of TAC-based regimens studied in this subgroup of patients with LN.…”
Section: Discussionmentioning
confidence: 52%
“…Our data at the least suggest that the use of TAC is not inferior to conventional treatment. Moreover, we and others27 28 32 showed that the safety profile of TAC is very good in LN. Therefore, we would recommend TAC to be considered as a treatment option in patients with refractory LN.…”
Section: Discussionmentioning
confidence: 64%
“…Для индукционной терапии ВН (классы III и IV) применяют режим Euro-Lupus, включающий низкую дозу циклофосфамида (ЦФ; 6 пульсов в течение 2 нед в фиксированной дозе 500 мг) [58], который не уступает по эффективности режиму, предложенному NIH (The National Institutes of Health) -750 мг/м 2 ежемесячно каждые 3 мес. В настоящее время в лечении ВН все более важное место занимают МФМ и ингибиторы кальциневрина, не уступающие по эффективности ЦФ (или превосходящие его) и более безопасные в отношении НЛР [59][60][61]. Напомним, что МФМ -иммуносупрессивный препарат, механизм действия которого связан с обратимой ингибицией фермента инозин-5-монофосфат-дегидрогеназы, участвующего в синтезе (de novo) гуанин нуклеотидов и 2-дезоксирибонуклеотида.…”
unclassified